Towards an Authentic Indian Environmentalism - Michael G. Jackson (Environmental Association of Southern Africa, 2004)
Despite elaborate policies and programmes to deal with them, environmental problems in India are generally worsening. In this paper it is argued that we are not adequately diagnosing these problems. There is a tendency to focus on effects, i.e. on technical definitions and solutions, rather than on causes - which are predominantly social, economic and political. In this we have followed the lead of Western environmentalism. We must first of all, therefore, question this Western perspective. Then we must attempt to articulate an authentic Indian environmentalism. To do this we must take into account the perceptions of all those people in our society who are being marginalised by 'development' and globalisation and their many creative responses to the environmental problems they face. This paper describes some of these responses and reflects upon them.